Synthesis Of 4-Alil-6- (Hydroxymethyl) -2-Methody Phenol Compounds from Eugenol Through Mannich Reaction Followed Methylation with Methyl Iodide and Subtitution Using NaOH - Perangin-angin, Sabarmin (Journal of Chemical Natural Resources, 2019)
Eugenol derivative compound 4-allyl-6-hydroxymethyl-2-methoxy phenol was synthesized through Mannich reaction, methylation, dan nucleophilic substitution. Mannich reaction was carried out by reacting eugenol, formaldehyde 37%, and dimethylamine 40 % in reflux condition with n-heptane solvent at temperature 98o-100oC for 10 hours produced 4-allyl-6-(dimethylamino)methyl-2-methoxy phenol with yield of 83 %. The formation of dimethylaminomethyl group supported by C-N stretching vibration at 1246,16 cm-1 and ion molecule peak at 221 in GC-MS analysis. Methylation of 4-allyl-6-(dimethylamino)methyl-2-methoxy phenol was carried out with methyl iodide in ethanol solvent produced 6-((N-iodo-N-methyl-N-methyl-N-methylamino) methyl)-4-allyl-2-methoxy phenol in solid form, which then purified by recrystallization with 78,15 % yield. 4-allyl-6-(hydroxymethyl)-2-methoxy phenol was synthesized by nucleophilic substitution reaction of 6-((N-iodo-N-methyl-N-methyl-N-methylamino)methyl)-4-allyl-2-methoxy phenol with sodium hydroxide in reflux condition then purified by coloum chromatography gave liquid compound with yield of 65,05%. The formation of hydroxymethyl group supported by OH vibration at 3433,9 cm-1 and ion molecule peak at 194 in GC-MS analysis show the relative molecular mass of synthesized product.